2015
DOI: 10.1097/md.0000000000002228
|View full text |Cite
|
Sign up to set email alerts
|

Consort

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 44 publications
3
12
0
Order By: Relevance
“…Increasing evidence shows that this pathway that once exhibited abnormalities can also participate in the potential mechanism of PD [12]. Beta-catenin is a crucial molecule in the Wnt signaling pathway and plays a significant role in cell adhesion, growth, invasion, and metastasis [14]. Glycogen synthase kinase 3β (GSK-3β) has been shown to participate in PD, since it can affect the central nervous system and neuronal apoptosis [15, 16].…”
Section: Introductionmentioning
confidence: 99%
“…Increasing evidence shows that this pathway that once exhibited abnormalities can also participate in the potential mechanism of PD [12]. Beta-catenin is a crucial molecule in the Wnt signaling pathway and plays a significant role in cell adhesion, growth, invasion, and metastasis [14]. Glycogen synthase kinase 3β (GSK-3β) has been shown to participate in PD, since it can affect the central nervous system and neuronal apoptosis [15, 16].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Zeng et al (61) identified a negative correlation trend between miR-204-5p and SIX homeobox 1 (Six1) expression in BC tissue samples, and when miR-204-5p mimics or Six1 siRNA was transfected, the expression of chromodomain helicase DNA binding protein 1 was markedly increased, thus enhancing epithelial-mesenchymal transition and affecting the invasion and migration of BC cells (61). Various target genes of miR-204-5p have been confirmed in previous studies, including traditional serrated adenoma, MX dynamin like GTPase 1, thioredoxin interacting protein, Src-associated in mitosis 68 kDa protein and forkhead box A1 (57,6264). However, more target genes need to be determined.…”
Section: Discussionsupporting
confidence: 52%
“…The 68-kDa Src-associated protein in mitosis (SAM68) is a GTPase-activating protein (GAP)-related protein involved in intracellular signal transduction that maintains the self-renewal of breast CSCs via affecting the oncogene serine/arginine-rich splicing factor. By targeting SAM68, miR-204 reduces the stem cell phenotype in breast cancer and neutralizes the tumorigenic effect of Sam68 in vivo [47]. It was also reported that miR-204 suppresses self-renewal, stem cell-associated phenotype, and migration of glioma cells via targeting the stemness-governing transcriptional factor SOX4 and the migration-promoting receptor EphB2 [30].…”
Section: Physiological Functions Of Mir-204mentioning
confidence: 99%